Peran Penting Afiliasi dan Influencer dalam Mengubah Perilaku Konsumen untuk Pemasaran Produk di Era Digital: Perspektif TikTok - Regita Octavia; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This research aims to find out the important role of affiliates and influencers in consumer behavior towards product marketing in the digital era from a TikTok perspective. This research uses a systematic literature review method with the help of the publish or perish application. Influencer marketing has become an important strategy for brands to reach target audiences. Influencers have the power to influence consumer behavior through their content and recommendations, which is an important part of product marketing in the digital era. TikTok is emerging as an important platform for influencer marketing, with its short video format and large user base making it an attractive platform for brands to reach an easier demographic. Apart from that, affiliates also play an important role in changing consumer behavior by promoting products or services through social media platforms. Therefore, the role of affiliates and influencers in transforming consumer behavior for product marketing in the digital era is very important